Pro WF Windows Workflow in .NET 3.0 - Bukovics, Bruce (Apress : Imprint: Apress, 2007)
Windows Workflow Foundation (WF) is a groundbreaking addition to the core of the .NET Framework that allows you to orchestrate human and system interactions as a series of workflows that can be easily mapped, analyzed, adjusted, and implemented. As business problems become more complex, the need for a workflow-based solution has never been more evident. WF provides a simple and consistent way to model and implement complex problems. As a developer, you focus on developing the business logic for individual workflow tasks. The runtime handles the execution of those tasks after they have been composed into a workflow. Pro WF: Windows Workflow in .NET 3.0 provides you with the skills you need to incorporate WF into your applications. This book gets you up to speed with Windows Workflow Foundation quickly and comprehensively. The practical aspects of using WF are covered in a lively tutorial style with each workflow concept illustrated in C#. This book also includes detailed coverage of how to customize your workflows and access them in a variety of ways and situations so you can maximize the advantages of this technology.